Using Rich Pictures in Improving Students’ Speaking Ability - Meylina Meylina (Jurnal Ilmiah Pendidikan Scholastic, 2019)
This is an action research which was aimed to find the effect of using rich pictures toward students’ speaking ability on sharing understanding of a situation. The population of this research was all of the students in the first semester of Islamic Business Management in UIN Imam Bonjol Padang. Two classes have chosen randomly as the sample by using cluster sampling technique. The total students involved were 35 students. The researcher conducted it in two cycles; each cycle consisted of four meetings. Each cycle involved planning, acting, observing and reflecting. The data were taken through direct observation. Observation checklist and field notes were used to collect qualitative data. Pre-test and post-tests were conducted to see the improvements in speaking. The data were analyzed by using four steps. They were data collection, data reduction, data display, drawing conclusion. The findings showed that rich pictures gave a positive effect on students’ speaking ability on sharing understanding of a situation and reformulation technique could better improve students’ grammar in speaking at the first semester of Islamic Business Management in UIN Imam Bonjol Padang